The Effect of Temperature and Time of Gasification Process and The Addition of Catalyst to The Composition of The Combustible Gas from The Wastes of Tobacco Leaves With Gasifier Updraft - Fatah Sulaiman; Endang Suhendi; Nindya Prastuti; Okta Abdul Choir (Universitas Sultan Ageng Tirtayasa, 2019)
The increasing industrial production is causing more of energy consumption needed. Tobacco leaves are waste from cigarette production that can be use as alternative biomass energy to solve the problems of the energy crisis in the near future. Gasification is the conversion of solid carbon raw materials from biomass by the partial oxidation to be combustible gas (CO, H2, and CH4) as an energy source. This research uses the fixed-bed reactor with capacity of 300 grams by the flow of updraft and raw material of waste tobacco leaves that have a size -14 + 18 mesh. The influence of temperature was research on 700 oC, 800 oC, and 900 oC with the reaction time for 20 minutes and the addition of a catalyst K2CO3. gasification medium used air and steam with the constant flow rate 0.504 m3/hour air and 0.0555 kg/minutes steam. Step of the process with the preparation of raw materials, the gasification process, and analysis of gas products. The result of the gasification process analysed using the gas chromatography, and the best results were obtained on the temperature 700 oC in the process time for 10 minutes produced combustible gas are CO = 22.82 % v, H2 = 26.82 % v, CH4 = 7.09 % v. increasing production gas happened when a catalyst K2CO3 is added, the producting of combustible gasses are CO = 52.76 % v, H2 = 23.46 % v, CH4, = 3.23 % v